Diaporthaceae associated with root and crown rot of maize - S.C. Lamprecht; P.W. Crous; J.Z. Groenewald; Y.T. Tewoldemedhin; W.F.O. Marasas (IMA Fungus)
Several isolates of coelomycetous fungi with pigmented conidia were consistently isolated from diseased roots of Zea mays in irrigated plots monitored in the KwaZulu-Natal Province of South Africa. Based on their morphology, these isolates could be identified as representative of Stenocarpella macrospora, S. maydis, and Phaeocytostroma ambiguum. Although species of Stenocarpella are well-known as causal agents of cob and stalk rot and leaf blight of maize in South Africa, the occurrence and importance of P. ambiguum is less well documented and understood. To determine the role of P. ambiguum as a root pathogen of maize, pathogenicity tests were conducted under glasshouse conditions at 18 °C night and 28 °C day temperatures using a pasteurised soil, river sand and perlite medium and a 0.5 % sand-bran inoculum. Based on these results, P. ambiguum was shown to be a primary pathogen of maize, but to be less virulent than the positive control, S. maydis. Furthermore, to clarify the higher-level phylogeny of these fungal genera, isolates were subjected to DNA sequencing of the nuclear ribosomal DNA (ITS & LSU). Partial gene sequences of the translation elongation factor 1-alpha gene were added to confirm the species monophyly. To resolve the generic placement of Phaeocytostroma, additional species such as P. sacchari, P. plurivorum and P. megalosporum were also added to the analysis. Based on these results, Stenocarpella and Phaeocytostroma were shown to be two well defined genera, belonging to Diaporthales , Diaporthaceae, being closely allied to Phomopsis (Diaporthe). All three genera were also observed to form alpha as well as beta conidia, and although this phenomenon is well documented for Phomopsis and Phaeocytostroma, it is a new observation for Stenocarpella. In spite of the differences in conidial pigmentation, no support could be obtained for polyphyly in Diaporthaceae, suggesting that as observed in Botryosphaeriaceae (Botryosphaeriales), conidial pigmentation is not informative at the family level in Diaporthales.